Methods for the Protection of Environmental Rights and Interests Through Legal Proceedings: Administrative Aspect and Criminal Aspect - Leheza, Yevhen; Horbalinskiy, Volodymyr; Berezniak, Vasyl; Khashev, Vadym; Oleksenko, Volodymyr (Journal of the University of Zulia, 2023)
The object of the investigation consists of the disclosure of procedural legislation, through the implementation of effective mechanisms of legal incidence on procedural aspects, which constitute the framework for the protection of the violated environmental rights and interests of citizens or other subjects of environmental legal relationships. Main content. A certain innovation may be the introduction of the institution of group lawsuits (massive, collective) in Ukraine, which will simplify access to justice for citizens, it will increase its quality and, due to the reduction of the burden on the courts, will accelerate the consideration of cases, including those of an environmental nature. Methodology: The methodological basis of the research is the dialectical method of scientific knowledge; Through the application of this method, the legal, functional, organizational and procedural aspects of the protection of environmental rights and interests in the courts were considered. conclusions. The article argues the need for new forms of protection of the rights and interests of a significant number of people; this is absolutely necessary in the context of the specificity of environmental disputes.